E-102 Economic and clinical model for direct transfer to angiosuite protocol development. (4th August 2020) - Requena, M; Seguel, V; Olivé-Gadea, M; García-Tornel, Á; Vilaseca, A; Rodríguez-Villatoro, N; Deck, M; Juega, J; Boned, S; Muchada, M; Piñana, C; Pagola, J; et al.
Abstract : Introduction: Direct transfer to angiosuite (DTAS) has consistently shown to be effective and safe shortening in-hospital workflows and encouraging long-term outcome benefits. In order to generalize DTAS an organizational and manpower effort is necessary. We aim to perform a cost-effective analysis of the implementation of a new angiography suite primarily dedicated to DTAS of stroke patients that will allow generalization of this pathway. Material and Methods: 61 patients who underwent endovascular treatment (EVT) following DTAS were matched for baseline variables to 117 patients who underwent conventional imaging protocol before EVT. An economic model based on current data was developed to assess the short and long term clinical and economic implications. The DTAS development scenario estimates a gradual 20% increase of DTAS rate for 4 years followed by a stable 80% rate of DTAS. Initial investment and additional organizational costs were included: 4M €. A cost-effective study compared the DTAS development scenario (SC1) to a scenario with no organizational changes (SC2) over 10 years. Results: The 10 year model included 1775 EVT patients in each scenario: SC1 68% DTAS Vs SC2 0% DTAS. SC1 would be associated with better functional independence rates (mRS 0–2: 45.8% versus 40.2% p=0.04) and a quality-adjusted life-years gain of 0.12 per patient. Despite the additional investment, SC1 development was associated with an estimated 15.1% reduction (26.25M €) of total costs (173.749M €). Cost saving was mainly due to long-term associated costs related with patient disability (€ 26.4 million). Conclusions: Our economic model predicts that the development of a DTAS program is cost effective. Disclosures: M. Requena: None. V. Seguel: None. M. Olivé-Gadea: None. Á. García-Tornel: None. A. Vilaseca: None. N. Rodríguez-Villatoro: None. M. Deck: None. J. Juega: None. S. Boned: None. M. Muchada: None. C. Piñana: None. J. Pagola: None. D. Rodríguez-Luna: None. D. Hernández: None. M. Rubiera: None. C. Molina: None. A. Tomasello: None. M. Ribo: 2; C; Medtronic, Stryker, Johnson and Johnson, Anaconda Biomed, Apta Targets.